2003
DOI: 10.1093/genetics/164.3.963
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Selective Digestion of Mitochondrial DNA in Accordance With the matA Hierarchy of Multiallelic Mating Types in the Mitochondrial Inheritance of Physarum polycephalum

Abstract: Although mitochondria are inherited uniparentally in nearly all eukaryotes, the mechanism for this is unclear. When zygotes of the isogamous protist Physarum polycephalum were stained with DAPI, the fluorescence of mtDNA in half of the mitochondria decreased simultaneously to give small spots and then disappeared completely ∼1.5 hr after nuclear fusion, while the other mitochondrial nucleoids and all of the mitochondrial sheaths remained unchanged. PCR analysis of single zygote cells confirmed that the loss wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…1 B). As reported previously 15 , mt-nucleoids in several mitochondria became short and disappeared in zygotes 5 h after plating (Fig. 1 A m–o).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…1 B). As reported previously 15 , mt-nucleoids in several mitochondria became short and disappeared in zygotes 5 h after plating (Fig. 1 A m–o).…”
Section: Resultssupporting
confidence: 87%
“…Both strains have no mitochondrial fusion plasmids, so mitochondrial fusion doesn’t occur. When AI35 and DP246 were crossed, previous studies showed that mt-nucleoids in mitochondria derived from DP246 were selectively digested in zygotes 23 and mtDNA derived from AI35 was selectively inherited to plasmodium 15 . AI35 and DP246 contained 15.5 ± 1.2 and 15.7 ± 1.4 mitochondria per cell, respectively (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations